(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Abstracts of papers presented at the XLIST ANNUAL SCIENTIFIC CONFERENCE OF THE PHYSIOLOGICAL SOCIETY OF NIGERIA held between 13th and 16th February 2024 at the Rivers State University, Port Harcourt, and PAMO University of Medical Sciences, Port Harcourt, Rivers State, Nigeria.